A Sr2Si5N8:Eu 2+ Spray pyrolysis synthesis of nanoparticles

By spraying the synthesis method, the crystallization and optical properties of sr2si5n8: EU2+nanoparticles were improved, and the problem of lack of optical performance of nanoparticle in existing technology has achieved higher light absorption and light conversion capabilities. effect.

CN118619218BActive Publication Date: 2025-01-28广西农业职业技术大学
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410868520.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-28
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

When the prior art synthesizes Sr2Si5N8:Eu2+ nanoparticles, the crystallinity and optical performance are insufficient, making it difficult to meet the demand for higher performance of nanotechnology.

Method used

The spray thermal solution synthesis method is adopted, and the forefront solution is atomized and the heat solution at high temperature forms SR2SI5N8: EU2+nanoparticles, and burns in the gas environment to enhance the crystallinity.

Benefits of technology

It improves the crystallization and light of nanoparticles, enhances light absorption and light conversion capabilities, and is suitable for agricultural photosynthetic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619218B_ABST
    Figure CN118619218B_ABST
Patent Text Reader

Abstract

The invention discloses a Sr2Si5N8:Eu 2+ The spray pyrolysis synthesis method of nanoparticles comprises the following steps: step 1: weighing 49 mmol strontium nitrate; 125 mmol tetraethyl orthosilicate; 1 mmol europium nitrate; 400 mmol urea; dissolving the above precursors in 250 mL deionized water to form a uniform precursor solution; step 2: using an atomizer to atomize the precursor solution obtained in step 1; spraying the atomized solution into a high-temperature furnace maintained at 1000° C.; using argon gas with a flow rate of 1 L / min as a carrier gas to promote decomposition and reaction to form Sr2Si5N8:Eu 2+ Particles; Step 3: Use a fiber filter to collect the nanoparticles formed in step 2; Step 4: Rinse the collected nanoparticles three times with deionized water; Step 5: Calcine the nanoparticles treated in step 4 at 1200°C for 2 hours in an argon environment. To synthesize Sr2Si5N8:Eu with higher crystallinity, better luminescence intensity, stronger light absorption and light conversion capabilities 2+ Nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to Sr 2 Si 5 N 8 :Eu 2+ A method for synthesizing nanoparticles, particularly a method for synthesizing Sr 2 Si 5 N 8 :Eu 2+ Spray pyrolysis synthesis of nanoparticles. Background Art

[0002] Sr 2 Si 5 N 8 :Eu 2+ Nanoparticles have shown broad application prospects in the fields of light-emitting diodes, lasers, sensors, etc. due to their unique optical and electronic properties. The particles are currently commonly synthesized by solid-state synthesis (SSS). 2 Si 5 N 8 :Eu 2+ Nanoparticles have good crystallinity and light conversion ability, but with the rapid development of nanotechnology, the demand for Sr 2 Si 5 N 8 :Eu 2+ The requirements for nanoparticles have also increased, and a method is needed to provide Sr with better performance. 2 Si 5 N 8 :Eu 2+ Nanoparticles. Summary of the invention

[0003] The present invention is intended to provide a Sr 2 Si 5 N 8 :Eu 2+ The spray pyrolysis synthesis method of nanoparticles is used to synthesize Sr with higher crystallinity, better luminescence intensity, stronger light absorption and light conversion capabilities. 2 Si 5 N 8 :Eu 2+ Nanoparticles.

[0004] In order to achieve the above object, the present invention provides the following technical solution: a Sr 2 Si 5 N 8 :Eu 2+ The spray pyrolysis synthesis method of nanoparticles comprises the following steps:

[0005] Step 1: Material preparation:

[0006] Weigh 49 mmol of 99.9% pure strontium nitrate (Sr(NO 3 ) 2 );

[0007] Weigh 125 mmol of tetraethyl orthosilicate (TEOS) with a purity of 99.999%;

[0008] Weigh 1 mmol of 99.9% pure europium nitrate (Eu(NO 3 ) 2 );

[0009] Weigh 400mmol, purity 99.5% urea;

[0010] The above precursors were dissolved in 250 mL of deionized water to form a uniform precursor solution;

[0011] Step 2: Atomization and pyrolysis:

[0012] Atomizing the precursor solution obtained in step 1 using an atomizer;

[0013] The atomized solution is sprayed into a high-temperature furnace maintained at 1000°C;

[0014] Argon (Ar) with a flow rate of 1 L / min was used as a carrier gas to promote decomposition and reaction to form Sr 2 Si 5 N 8 :Eu 2+ particle;

[0015] Step 3: Particle collection:

[0016] The nanoparticles formed in step 2 are collected using a fiber filter;

[0017] Step 4: Post-processing:

[0018] The collected nanoparticles were rinsed three times with deionized water;

[0019] Step 5: Calcination:

[0020] The nanoparticles treated in step 4 were calcined at 1200° C. for 2 hours in an argon environment to enhance their crystallinity.

[0021] The principle and beneficial effects of this technical solution:

[0022] Synthesis of Sr by Spray Pyrolysis (SP) 2 Si 5 N 8 :Eu 2+The crystallinity of the nanoparticles was significantly improved, and the luminescence intensity was increased. In addition, the mesoporous structure of the SP synthesized particles showed a larger surface area, reaching 124.7 m 2 / g, which helps improve light absorption capacity, which is crucial for applications in enhancing photosynthesis in greenhouse environments. SP nanoparticles have superior light conversion capabilities, which have a significant impact on optimizing light distribution for plant growth. Easy scalability and enhanced optical properties are beneficial for agricultural applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Sr was synthesized by solid state and spray pyrolysis. 2 Si 5 N 8 :Eu 2+ Comparison of SEM, TEM and high-resolution TEM images of particles;

[0024] Figure 2 Sr 2 Si 5 N 8 :Eu 2+ STEM images, EDX spectra, and elemental mapping of Si, Sr, N, and Eu in a single particle;

[0025] Figure 3 Sr 2 Si 5 N 8 :Eu 2+ Particle and solid-state synthesis of Sr 2 Si 5 N 8 :Eu 2+ N2 adsorption-desorption isotherms of particles;

[0026] Figure 4 Solid-state synthesis and spray pyrolysis of Sr 2 Si 5 N 8 :Eu 2+ Powder X-ray diffraction pattern of particles;

[0027] Figure 5 Solid-state synthesis and spray pyrolysis of Sr 2 Si 5 N 8 :Eu 2+ Fourier transform infrared spectroscopy (FT-IR), excitation and emission spectroscopy;

[0028] Figure 6 It is the UV-visible absorption spectrum and UV-visible transmission spectrum. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings and embodiments:

[0030] 1. Synthesis of Sr 2 Si 5 N 8 :Eu 2+ Particles and thin films

[0031] 1. Spray pyrolysis (SP) synthesis:

[0032] Using strontium nitrate (Sr(NO 3 ) 2 )、tetraethyl orthosilicate (TEOS), europium nitrate (Eu(NO 3 ) 2 ) and urea as precursors. The initial mass of each precursor is Sr(NO 3 ) 2 (49 mmol, purity 99.9%, purchased from Sigma-Aldrich), TEOS (125 mmol, purity 99.999%, purchased from Alfa Aesar), Eu(NO 3 ) 2 (1 mmol, 99.9% purity, purchased from Sigma-Aldrich) and urea (400 mmol, 99.5% purity, purchased from Fisher Scientific). These precursors were dissolved in 250 mL of deionized water to form a uniform precursor solution. The solution was then atomized using an atomizer and sprayed into a high-temperature furnace maintained at 1000°C, using argon (Ar) as a carrier gas at a flow rate of 1 L / min. In the furnace, decomposition and reaction processes occurred to form Sr 2 Si 5 N 8 :Eu 2+ The particles were collected using a fiber filter and then rinsed three times with deionized water. Next, the synthesized particles were calcined at 1200° C. for 2 hours in an argon environment to enhance their crystallinity.

[0033] 2. Solid-state synthesis (SSS) synthesis:

[0034] The mass of each precursor was precisely measured: 49 mmol of Sr(NO 3 ) 2 、125mmol of TEOS、1mmol of Eu(NO 3 ) 2 and 400 mmol of urea. These precursors were mixed thoroughly to ensure uniform distribution of the elements in the mixture. The powder mixture was then calcined at 1200 °C for 2 h in an argon environment to promote a solid-state reaction that converted the precursor mixture into Sr 2 Si5 N 8 :Eu 2+ Urea was used as nitrogen source. After the reaction was completed, the crucible was slowly cooled to room temperature to prevent thermal stress and phase transition. Finally, the particles were ball milled for 1 h to obtain a fine particle size distribution.

[0035] 3. Preparation of three films:

[0036] Ordinary film, SSS Sr 2 Si 5 N 8 :Eu 2+ Particle Dispersion Film and SP Sr 2 Si 5 N 8 :Eu 2+ Particle dispersion films.

[0037] The steps are as follows, for SSS Sr 2 Si 5 N 8 :Eu 2+ Particles and SP Sr 2 Si 5 N 8 :Eu 2+ Particle dispersion film, Sr 2 Si 5 N 8 :Eu 2+ The phosphors were sieved to ensure uniform particle size, accurately weighed and mixed with low-density polyethylene (LDPE) particles, and 11% by mass of silicone light diffuser was added to the mixture. The mixture was melt-treated at high temperature in a twin-screw extruder to make pellets. After pelletization, the fluorescent LDPE pellets were placed in a 100°C dryer to remove any residual moisture. Finally, a film blowing machine was used to make the light-converting film.

[0038] For the ordinary film as a control, the film production process was followed, but no Sr was added. 2 Si 5 N 8 :Eu 2+ Phosphor.

[0039] 2. Test and Results

[0040] The morphology and particle size were tested using Thermo Fisher Scientific Apreo SEM and JEOL JSM-IT2000 TEM. Phases were identified and crystal structures were analyzed using a Bruker D8 Discover X-ray diffractometer (XRD). Surface area and pore size distribution were evaluated using the Brunauer-Emmett-Teller (BET) method performed using a Micromeritics TriStar II Plus surface analyzer. Its optical properties were tested using a PerkinElmer Lambda 950 UV-Vis spectrometer.

[0041] 1. Absorption and transmission test

[0042] The films were tested by UV-visible spectroscopy to measure the absorption and transmission properties. The films were exposed to UV-visible light range and the absorption and transmission spectra were recorded using a UV-visible spectrometer (PerkinElmer, Lambda 950). These measurements provided insights into the light conversion capabilities of the Sr2Si5N8:Eu2+ particles embedded in the polymer matrix.

[0043] 2. Analysis

[0044] like Figure 1 As shown, Figure 1 a. Figure 1 b. Figure 1 c respectively SP Sr 2 Si 5 N 8 :Eu 2+ SEM, TEM and high-resolution TEM of particles; Figure 1 d. Figure 1 e. Figure 1 f are SSS Sr 2 Si 5 N 8 :Eu 2+ SEM, TEM, and high-resolution TEM of particles. The SEM and TEM images of SSS and SP particles show that SP particles have regular shapes and smooth surfaces, with particle sizes ranging from 20 to 200 nm. In contrast, the SEM and TEM images of SSS particles show irregular shapes and rougher textures, with sizes of 200 nm or less. The high-resolution TEM images clearly show the crystal lattices of SP and SSS particles, with a lattice spacing of 0.32 nm, corresponding to Sr 2 Si 5 N 8 The (113) plane in the SP and SSS particles indicates that both particles have good crystallinity. The different shapes of SP and SSS particles are determined by their synthesis methods.

[0045] like Figure 2 As shown, Figure 2 a is the Sr from spray pyrolysis 2 Si 5 N 8 :Eu 2+ STEM image of a single particle. Figure 2 b is Sr from spray pyrolysis 2 Si 5 N 8 :Eu 2+ EDX spectrum of a single particle. Figure 2 c. Figure 2 d. Figure 2 e. Figure 2 f is Sr 2 Si 5 N 8 :Eu 2+ Elemental mapping of Si, Sr, N and Eu for individual particles, Figure 2 a Highlights the spherical structure of SP particles. Figure 2 b shows the Figure 2 Extracted EDX line scan profiles in a show the X-ray signal intensity along selected lines within the particle. The enhanced signals in these profiles correspond to different elements, and the straight lines indicate that the elements are evenly distributed along the line scan. Figure 2 c. Figure 2 d. Figure 2 e. Figure 2 f shows the uniform distribution of each element within the particle. Overall, this image provides an 2 Si 5 N 8 :Eu 2+ Detailed analysis of the composition and morphology of the particles confirmed that the elements were evenly distributed throughout the particles.

[0046] like Figure 3 As shown, Figure 3 a is SP Sr 2 Si 5 N 8 :Eu 2+ N2 adsorption-desorption isotherm of particles, Figure 3 b is SSSSr 2 Si 5 N 8 :Eu 2+ N2 adsorption-desorption isotherms of the particles. Both samples show type IV isotherms, which are characteristic of mesoporous materials. SP sample ( Figure 3a) shows a more obvious hysteresis loop in the isotherm, indicating that it contains more mesopores compared to the SSS sample. This observation is further supported by the pore size distribution inset, which shows that the pore size distribution of the SP sample is narrow and relatively uniform, centered at about 40 nm, indicating that it has a uniform mesoporous structure. On the other hand, the SSS sample ( Figure 3 b) The hysteresis loop in the adsorption isotherm is smaller and the pore size distribution is wider. The specific surface areas of SP and SSS particles are calculated to be 124.7 m 2 / g and 108.3m 2 / g.

[0047] The results show that the 2 Si 5 N 8 :Eu 2+ The SP method of particles can produce a more controlled and uniform mesoporous structure than the traditional SSS route. The mesoporosity of SP samples contributes to the properties of increased surface area, enhanced light absorption and improved luminescence efficiency, which are very beneficial for phosphor applications.

[0048] like Figure 4 As shown, the powder XRD patterns compare SSS and SP Sr 2 Si 5 N 8 :Eu 2+ The structural characteristics of the particles correspond to Sr 2 Si 5 N 8 orthorhombic structure. However, the diffraction peak intensity of the SP sample is higher and the peak shape is sharper than that of the SSS sample. These differences indicate that the SP particles have higher crystallinity and fewer structural defects. The improved structural quality of the SP samples can be attributed to the unique rapid heating and high temperature conditions provided by the SP method, which promotes better crystallization compared with the SSS route.

[0049] like Figure 5 As shown, Figure 5 a is SSS and SP Sr 2 Si 5 N 8 :Eu 2+ Fourier transform infrared spectroscopy (FT-IR), Figure 5 b is SSS and SP Sr 2 Si 5 N 8 :Eu 2+ The excitation and emission spectra of Figure 5As shown in Figure 1, along the blue line representing SSS, distinct peaks corresponding to CO2, H2O, Si-N-Si stretching vibration, and Sr-Eu-N bending vibration are observed at specific wavenumbers. Similarly, the red line representing SP also shows peaks associated with these same functional groups. Together, these spectra illustrate the SSS and SP origins of Sr 2 Si 5 N 8 :Eu 2+ The particles have similar molecular structures and bonding patterns.

[0050] Figure 5 In b, SSS and SP Sr are shown 2 Si 5 N 8 :Eu 2+ Photoluminescence (PL) spectra of particles, including excitation and emission spectra. The excitation spectrum covers a wide wavelength range from 200 to 600 nanometers, while the emission spectrum shows a single narrow peak at about 630 nanometers. When these materials absorb light energy, the electrons inside are excited and jump to higher energy levels. When these electrons return to their original state, they emit light at a specific wavelength.

[0051] SSS and SP Sr 2 Si 5 N 8 :Eu 2+ The excitation and emission spectra of the particles show similar peak positions, indicating that they have comparable band gaps. However, the peak intensity of the SP particles is higher than that of the particles from the SSS method, indicating that the energy transfer and recombination processes inside the SP particles are more efficient. This efficiency is most likely due to the increased conversion between energy states, leading to enhanced light emission. The improvement of the SP particles can be attributed to their larger surface area, which provides more interaction sites for the excitation and emission processes, thereby increasing the (PL) intensity. These enhanced excitation and emission intensities in SP particles are particularly beneficial for optical applications.

[0052] like Figure 6 As shown, observing these spectra, it can be found that compared with ordinary films, the light conversion film effectively weakens the transmittance of light in the wavelength range of 200-320 nm, while increasing the transmittance of light in the wavelength range of 320-700 nm. Between SSS and SP particles, SP shows better performance in UV light attenuation and visible light enhancement, which may be attributed to its increased surface area and spherical particle shape.

[0053] The increased surface area provides more sites for interaction with light, and spherical particles scatter light more evenly than irregularly shaped particles. This uniform scattering helps maximize the interaction of incident UV light with the conversion material, resulting in more efficient energy transfer and conversion to red light. Additionally, irregularly shaped particles can cause energy to be lost through absorption or re-emission in undesirable directions. Spherical particles mitigate these issues, allowing more light to penetrate into the conversion material and participate in the conversion process.

[0054] The photoconversion film effectively proved that it can convert ultraviolet light into red-orange light. It suppresses 200-300 nanometer ultraviolet light while enhancing 300-700 nanometer visible light, which is of great significance for greenhouse plant photosynthesis.

[0055] First, the light-converting film reduces harmful ultraviolet (UV) radiation to plants, particularly UV-B (280-315 nm) and UV-C (100-280 nm), which can damage a plant's DNA, proteins and cell structure.

[0056] Secondly, the light conversion film enhances photosynthesis. Photosynthesis mainly occurs in the blue light (400-500 nanometers) and red light (600-700 nanometers) regions. By enhancing light in the 300-700 nanometer range, the light conversion film provides plants with more light that is essential for photosynthesis. This promotes photosynthesis, which helps increase yields and improve plant growth.

[0057] Third, the light conversion film optimizes the light spectrum. Red and blue light have been shown to be the most efficient for photosynthesis, while green light is less efficient. By converting blue-violet light into red-orange light, the light conversion film optimizes the light spectrum for optimal plant growth and development.

[0058] Light-converting films reduce harmful UV radiation while promoting photosynthesis, which can improve plant yield and quality in greenhouses.

[0059] 3. Conclusion

[0060] The spray pyrolysis (SP) method was used to synthesize Sr 2 Si 5 N 8 :Eu 2+The SP method produces particles with 30% higher crystallinity and 25% higher luminescence intensity compared to solid-state synthesis (SSS). In addition, the mesoporous structure characteristics of the SP synthesized particles show a 15% larger surface area of ​​124.7m2 / g, which helps to improve the light absorption capacity. These properties are crucial for applications in enhancing photosynthesis in greenhouse environments. UV-visible spectroscopy confirmed that the SP nanoparticles have superior light conversion capabilities and have a significant impact on optimizing light distribution for plant growth. This study highlights the advantages of SP, including easy scalability and enhanced optical properties, which are critical for agricultural applications. The study emphasizes the role of the choice of synthesis method in tailoring Sr for specific functional requirements in optical and agricultural technologies. 2 Si 5 N 8 :Eu 2+ The properties of nanoparticles play a key role.

[0061] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. For those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A Sr2Si5N8:Eu 2+ The spray pyrolysis synthesis method of nanoparticles is characterized in that: The following steps are involved: Step 1: Material preparation: Weigh 49 mmol of strontium nitrate (Sr(NO3)2) with a purity of 99.9%; Weigh 125 mmol of tetraethyl orthosilicate (TEOS) with a purity of 99.999%; Weigh 1 mmol of europium nitrate (Eu(NO3)2) with a purity of 99.9%; Weigh 400mmol, purity 99.5% urea; The above precursors were dissolved in 250 mL of deionized water to form a uniform precursor solution; Step 2: Atomization and pyrolysis: Atomizing the precursor solution obtained in step 1 using an atomizer; The atomized solution is sprayed into a high-temperature furnace maintained at 1000°C; Argon (Ar) with a flow rate of 1 L / min was used as a carrier gas to promote decomposition and reaction to form Sr2Si5N8:Eu 2+ particle; Step 3: Particle collection: The nanoparticles formed in step 2 are collected using a fiber filter; Step 4: Post-processing: The collected nanoparticles were rinsed three times with deionized water; Step 5: Calcination: The nanoparticles treated in step 4 were calcined at 1200° C. for 2 hours in an argon environment to enhance their crystallinity.

Citation Information

Patent Citations

  • Method for preparing silicon-based nitride or nitric oxide fluorescent powder for LED

    CN103525407A